KETIDAKSANTUNAN DALAM KOMENTAR PUBLIK PADA VIDEO PIDATO PERDANA PRESIDEN PRABOWO: KAJIAN SOSIOPRAGMATIK - Aminuddin, Muhammad; Musfiroh, Tadkiroatun (Sunan Kalijaga State Islamic University Yogyakarta, 2025)
This study aims to reveal the impoliteness strategies used by netizens in the comment section of Prabowo Subianto’s inaugural speech as President of the Republic of Indonesia on the BeritaSatu YouTube channel. The background of this research is the growing phenomenon of harsh and impolite comments on social media, particularly in political discourse. This study employs a descriptive qualitative approach using Culpeper’s impoliteness theory within a sociopragmatic framework. The data, consisting of public comments, were analyzed to identify types and strategies of impoliteness, such as bald on record impoliteness, sarcasm and mock impoliteness, negative impoliteness, positive impoliteness, off-record impoliteness. The findings show that netizen comments contain specific patterns of impoliteness that reflect socio-political tensions and ideological expressions in digital space. This research contributes to the expansion of sociopragmatic studies and highlights the urgency of linguistic ethics in digital public communication.